Enhancing the yield and water use efficiency of processing tomatoes (Lycopersicon esculentum Miller) through optimal irrigation and salinity management under mulched drip irrigation - Jiaying Ma; Jian Liu; Yue Wen; Zhanli Ma; Jinzhu Zhang; Feihu Yin; Tehseen Javed; Jihong Zhang; Zhenhua Wang (Journal of Integrative Agriculture, 2025)
In recent years, the rational utilization of saline water resources for agricultural irrigation has emerged as an effective strategy to alleviate water scarcity. To safely and efficiently exploit saline water resources over the long term, it is crucial to understand the effects of salinity on crops and develop optimal water-salinity irrigation strategies for processing tomatoes. A two-year field experiment was conducted in 2018 and 2019 to explore the impact of water salinity levels (S1: 1 g L–1, S2: 3 g L–1, and S3: 5 g L–1) and irrigation amounts (W1: 305 mm, W2: 485 mm, and W3: 611 mm) on the soil volumetric water content and soil salinity, as well as processing tomato growth, yield, and water use efficiency. The results showed that irrigation with low to moderately saline water (<3 g L–1) enhanced plant water uptake and utilization capacity, with the soil water content (SWC) reduced by 6.5–7.62% and 10.52–13.23% for the S1 and S2 levels, respectively, compared to the S3 level in 2018. Under S1 condition, the soil salt content (SSC) accumulation rate gradually declined with an increase in the irrigation amount. For example, W3 decreased by 85.00 and 77.94% compared with W1 and W2 in 2018, and by 82.60 and 73.68% in 2019, respectively. Leaching effects were observed at the W3 level under S1, which gradually diminished with increasing water salinity and duration. In 2019, the salt contents of soil under each of the treatments increased by 10.81–89.72% compared with the contents in 2018. The yield of processing tomatoes increased with an increasing irrigation amount and peaked in the S1W3 treatment for the two years, reaching 125,304.85 kg ha–1 in 2018 and 128,329.71 kg ha–1 in 2019. Notably, in the first year, the S2W3 treatment achieved relatively high yields, exhibiting only a 2.85% reduction compared to the S1W3 treatment. However, the yield of the S2W3 treatment declined significantly in two years, and it was 15.88% less than that of the S1W3 treatment. Structural equation modeling (SEM) revealed that soil environmental factors (SWC and SSC) directly influence yield while also exerting indirect impacts on the growth indicators of processing tomatoes (plant height, stem diameter, and leaf area index). The TOPSIS method identified S1W3, S1W2, and S2W2 as the top three treatments. The single-factor marginal effect function also revealed that irrigation water salinity contributed to the composite evaluation scores (CES) when it was below 0.96 g L–1. Using brackish water with a salinity of 3 g L–1 at an irrigation amount of 485 mm over one year ensured that processing tomatoes maintained high yields with a relatively high CES (0.709). However, using brackish water for more than one year proved unfeasible.